Hydrothermal Growth and Hydrogen Selective Sensing of Nickel Oxide Nanowires. (11th October 2015) - Dang, Thi Thanh Le; Tonezzer, Matteo; Nguyen, Van Hieu
Abstract : Low cost synthesis of nanostructured metal oxides for gas sensing application at low temperature is nowadays of crucial importance in many fields. Herein, NiO p-type semiconducting nanowires with polycrystalline structure were prepared by a facile and scalable hydrothermal method. Morphology and crystal structure of the NiO nanowires were investigated by scan electron microscopy, X-ray diffraction, and transmission electron microscopy. The nanostructured material was then tested as hydrogen sensor showing very good performance in terms of sensor response, stability, absence of drifts, and speed of response and recovery. The selectivity of the NiO sensor to hydrogen towards other gases (ethanol, ammonia, and liquefied petroleum gas) was found to be good.